Implementasi Sila Pertama Pancasila dalam Tradisi Hajat Sasih Maulid di Kampung Naga: Studi Kualitatif dan Deskriptif - Nina Marliana; Mohamad Sutisna; Evi Endriani; Ondih Suhendi; Via Febrianti (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
The Hajat Sasih Maulid tradition in Kampung Naga is a tangible embodiment of the noble values of Pancasila, particularly the first principle. This study explores in depth how this tradition serves as a bridge between faith and deeds, belief and concrete actions. Through a descriptive qualitative approach, the research uncovers the religious, social, and cultural dimensions inherent in this tradition. The findings indicate that Hajat Sasih Maulid functions not only as a religious ritual but also as a means to strengthen national values, preserve the environment, and build a just and prosperous society. Additionally, the tradition serves as a medium for moral education, teaching the connection between spirituality and social responsibility, supporting community solidarity, and encouraging active participation in cultural heritage preservation. This research highlights the importance of local traditions in the national context and their contribution to harmonizing Pancasila values with everyday life practices.